Molecular Responses of Mussel Mytilus galloprovincialis Associated to Accumulation and Depuration of Marine Biotoxins Okadaic Acid and Dinophysistoxin-1 Revealed by Shotgun Proteomics - Martins, José Carlos; Domínguez-Pérez, Dany; Azevedo, Catarina; Braga, Ana Catarina; Costa, Pedro Reis; Osório, Hugo; Vasconcelos, Vitor; Campos, Alexandre (Frontiers in Marine Science, 2020)
The molecular pathways behind the toxicity of diarrheic shellfish toxins (DSTs) in bivalves have been scarcely studied. Thus, a shotgun proteomics approach was applied in this work to understand bivalves’ molecular responses to the dinoflagellate Prorocentrum lima (1.0x106 cells/L). Protein expression along with toxins levels were analyzed in the gills and digestive gland of the mussel Mytilus galloprovincialis during and after exposure to this toxic strain. Results revealed an accumulation of OA and DTX1 only in the digestive gland with maximum amounts attained at the end of uptake phase (day 5) (2819.2 ± 522.2 µg OA/kg and 1107.1 ± 267.9 µg DTX1/kg). At the end of the depuration phase (day 20), 16% and 47% of total OA and DTX1 concentrations remained in the digestive gland tissues, respectively. The shotgun proteomic analyses yielded 3052 proteins in both organs. A total of 57 and 54 differentially expressed proteins (DEPs) were revealed in the digestive gland and gills, respectively. Both organs presented the same response dynamics along the experiment, although with tissue-specific features. The early response (3days uptake) was characterized by a high number of DEPs, being more marked in gills, in relation to the latter time points (5 days uptake and depuration). Functional enrichment analysis revealed the upregulation of carboxylic (GO:0046943) and organic acid transmembrane transporter activity (GO:0005342) pathways after 3 days uptake for digestive gland. Matching to these pathways are a group of proteins related to transmembrane transport and response to toxic substances and xenobiotics, namely P-glycoprotein (ABCB11), Sodium-dependent proline transporter (SLC6A7) and Sideroflexin-1 (SFXN1). According to COG (Clusters of Orthologous Groups) categories, most of the DEPs found for digestive gland in all time-points were related with “cellular processes and signaling” and involving signal transduction mechanisms, cytoskeleton and post-translational modification, protein turnover, chaperone functions. In gills, the early uptake phase was marked by a balance between DEPs related with “cellular processes and signaling” and “metabolism”. Depuration is clearly marked by processes related with “metabolism”, mainly involving secondary metabolites biosynthesis, transport, and catabolism. Proteomic data are available via ProteomeXchange with identifier PXD022293.